2023
DOI: 10.1186/s13023-023-02664-y
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial growth and function in achondroplasia: a multimodal 3D study on 15 patients

Abstract: Background Achondroplasia is the most frequent FGFR3-related chondrodysplasia, leading to rhizomelic dwarfism, craniofacial anomalies, stenosis of the foramen magnum, and sleep apnea. Craniofacial growth and its correlation with obstructive sleep apnea syndrome has not been assessed in achondroplasia. In this study, we provide a multimodal analysis of craniofacial growth and anatomo-functional correlations between craniofacial features and the severity of obstructive sleep apnea syndrome. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…GM is an advanced coordinated-based statistical methodology widely applied in various fields, including comparative biology, paleontology, forensic science, and craniomaxillofacial surgery. [10][11][12][13] Compared with traditional cephalometric and volumetric methodologies, GM is regarded to have great advantages for multivariate analysis, control of the size and position of structures, dynamic visualization, and synthesis of theoretical morphology, 19,20 allowing a more holistic characterization of the complex craniofacial phenotype and dynamic insight of morphological variation in a precise and perceptual way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GM is an advanced coordinated-based statistical methodology widely applied in various fields, including comparative biology, paleontology, forensic science, and craniomaxillofacial surgery. [10][11][12][13] Compared with traditional cephalometric and volumetric methodologies, GM is regarded to have great advantages for multivariate analysis, control of the size and position of structures, dynamic visualization, and synthesis of theoretical morphology, 19,20 allowing a more holistic characterization of the complex craniofacial phenotype and dynamic insight of morphological variation in a precise and perceptual way.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has been widely applied and recognized in the fields of evolutionary biology, paleontology, zoology, and anthropology. [10][11][12][13] In craniomaxillofacial surgery, GM has been proven to be efficient in studying craniofacial and calvarial effects of unilateral craniosynostosis, 14 the relationship between craniofacial shape and malocclusion, 15 and maxillary protraction on the maxillofacial complex in patients with malocclusion. 16 To the best of our knowledge, there is still an academic paucity of research on visualizing dynamic morphological growth trajectories with GM in the Crouzon population.…”
mentioning
confidence: 99%
“…Geometric morphometric analysis (GM) is an advanced coordinated‐based statistical methodology widely applied in multiple fields, such as comparative biology, palaeontology, forensic science and craniomaxillofacial surgery 18–21 . Compared to traditional cephalometric and volumetric methodologies, GM has great advantages for multivariate analysis, control of the size and position of structures, dynamic visualization and synthesis of morphology, 30,31 allowing a more holistic characterization of the complex craniofacial phenotype and comprehensive insight between morphological variation and variables in a precise and perceptual way.…”
Section: Discussionmentioning
confidence: 99%
“…Geometric morphometric analysis is a useful statistical methodology for quantifying and visualizing morphological variation and growth trajectories 18 in a more objective and perceptual way. It has been widely applied and recognized in the fields of evolutionary biology, palaeontology, zoology and anthropology, especially in craniomaxillofacial surgery 18–21 . This study aimed to verify the correlation of the airway‐facial phenotype and visualize the morphological changes associated with geometric morphometrics in Crouzon syndrome patients.…”
Section: Introductionmentioning
confidence: 99%
“…These results enabled to predict during the growth the increase of morphological differences on ve anatomical regions located on the skull and the mandible. 40 A recent study completed by Holmes et al concluded that anticonvulsant-exposed children with the characteristic dysmorphic facial features, particularly a shorter nose, were more likely to have de cits in cognitive function. 16 The IQ scores were subdivided into full scale IQ, verbal IQ and performance IQ.…”
Section: Discussionmentioning
confidence: 99%